Adjuvant Exemestane With Ovarian Suppression in Premenopausal Breast Cancer: Long-Term Follow-Up of the Combined TEXT and SOFT Trials - Pagani, O (2023)
Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported.The combined analysis of SOFT-TEXT compared outcomes in 4,690 premenopausal women with estrogen/progesterone receptor-positive (ER/PgR+) early breast cancer randomly assigned to 5 years of exemestane + ovarian function suppression (OFS) versus tamoxifen + OFS. After a median follow-up of 9 years, exemestane + OFS significantly improved disease-free survival (DFS) and distant recurrence-free interval (DRFI), but not overall survival, compared with tamoxifen + OFS. We now report DFS, DRFI, and overall survival after a median follow-up of 13 years. In the intention-to-treat (ITT) population, the 12-year DFS (4.6% absolute improvement, hazard ratio [HR], 0.79; 95% CI, 0.70 to 0.90; P <.001) and DRFI (1.8% absolute improvement, HR, 0.83; 95% CI, 0.70 to 0.98; P =.03), but not overall survival (90.1% v 89.1%, HR, 0.93; 95% CI, 0.78 to 1.11), continued to be significantly improved for patients assigned exemestane + OFS over tamoxifen + OFS. Among patients with human epidermal growth factor receptor 2-negative tumors (86.0% of the ITT population), the absolute improvement in 12-year overall survival with exemestane + OFS was 2.0% (HR, 0.85; 95% CI, 0.70 to 1.04) and 3.3% in those who received chemotherapy (45.9% of the ITT population). Overall survival benefit was clinically significant in high-risk patients, eg, women age < 35 years (4.0%) and those with > 2 cm (4.5%) or grade 3 tumors (5.5%). These sustained reductions of the risk of recurrence with adjuvant exemestane + OFS, compared with tamoxifen + OFS, provide guidance for selecting patients for whom exemestane should be preferred over tamoxifen in the setting of OFS.